The impact of Behavioral biases on Trade Policy preferences : a case study of Brexit - Azbekova, Amira (2025)
This thesis investigates the impact of behavioral biases on trade policy preferences, using the Brexit referendum and the United Kingdom’s subsequent trade trajectory as a case study. While traditional economic models often assume rational decision making, this study incorporates insights from behavioral economics, specifically prospect theory, bounded rationality, overconfidence bias, and political framing, to explain deviations in voter behavior and trade policy outcomes. The analysis employs a binary logistic regression model using individual-level data from the British Election Study to empirically assess the relationship between behavioral predictors (e.g., loss aversion, overconfidence, economic insecurity) and the likelihood of voting Leave. Results show that these cognitive biases significantly influenced referendum choices, with loss aversion and overconfidence emerging as robust predictors. In parallel, the thesis evaluates post-Brexit trade policy under the Global Britain strategy through comparative trade performance analysis with Germany. Despite the narrative of sovereign trade renewal, findings suggest the UK's trade agreements have prioritized symbolic over economic value. This research contributes to the behavioral political economy literature by empirically demonstrating how psychological factors shape large-scale economic decisions and long-term policy directions in democratic settings.